PENGARUH LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI PADA PUSKESMAS DESA WAAI KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Andrie Christina Salhuteru; Harold Hursepuny (Jurnal Administrasi Terapan, 2025)
Human resources are the main asset that greatly determines the success of an organization, including public service institutions such as community health centers (Puskesmas). One of the key factors influencing employee performance and productivity is the work environment. A supportive work environment, particularly one that is non-physical, is believed to improve employee job satisfaction, thereby contributing to the achievement of organizational goals.This study aims to analyze the influence of the physical work environment on the employees' job satisfaction at Waai Village Community Health Center, Salahutu District, Central Maluku Regency. The physical work environment examined the relationships between supervisors and subordinates, the relationships among colleagues, communication, and the presence of a supportive work atmosphere. This research employs a quantitative approach, utilizing descriptive methods and simple linear regression analysis. The population in this study consists of all employees of the Waai Village Community Health Center, totaling 52 people. Data were collected through questionnaires and tested for validity and reliability, using SPSS version 30.The results showed that the non-physical work environment has a significant positive effect on job satisfaction, with a regression coefficient of 0.498 and a significance level of 0.009 (< 0.05). The R Square value of 0.129 indicates that the non-physical work environment can explain 12.9% of the variation in job satisfaction. This study concludes that the better quality of the physical work environment, the higher the level of employee job satisfaction. Therefore, it is recommended that the management continuously improve the work environment to support employee satisfaction and productivity.